Genome-level selection in tumors as a universal marker of resistance to therapy - Erez Persi; Praneeth R. Sudalagunta; Yuri I. Wolf; Rafael R. Canevarolo; Mehdi Damaghi; Kenneth H. Shain; Ariosto S. Silva; Eugene V. Koonin (Nature Communications)
Abstract Tumor evolution is shaped by selective pressures imposed by physiological factors as the tumor naturally progresses to colonize local and distant tissues, as well as by therapy. However, the distinction between these two types of pressures and their impact on tumor evolution remain elusive, mainly, due to extensive intra-tumor heterogeneity. To disentangle the effects of these selective pressures, we analyze data from diverse cohorts of patients, of both treated and untreated cancers. We find that, despite the wide variation across patients, the selection strength on tumor genomes in individual patients is stable and largely unaffected by tumor progression in the primary settings, with some cancer-specific signatures detectable in the progression to metastases. However, we identify a nearly universal shift toward neutral evolution in tumors that resist treatment and demonstrate that this regime is associated with worse prognosis. We validate these findings on both published and original datasets. We suggest that monitoring the selection regime during cancer treatment can assist clinical decision-making in many cases.